2017
DOI: 10.1186/s40795-017-0129-3
|View full text |Cite
|
Sign up to set email alerts
|

Chronic energy deficiency and associated factors among adults living with HIV in Gondar University Referral Hospital northwest Ethiopia

Abstract: Background: Human Immunodeficiency Virus (HIV) infection and chronic energy deficiency are bidirectional and multifaceted. HIV can cause or worsen chronic energy deficiency by increasing energy requirements, reducing food intake and nutrient absorption. Chronic energy deficiency weakens the immune system, increase the susceptibility to infections and worsening the disease impact. Studies on the magnitude and factors associated with chronic energy deficiency among adults living with HIV are limited. The aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…A cohort study in Singapore showed that there was a significant association between clinical disease stage and nutritional status 40. Similarly, the studies at Gonder and West Shewa Zone Ethiopia and Kathmandu Valley, Nepal indicated that the risk of undernutrition increased from WHO clinical stage 1 to 4 23,29,31. There was a relationship between weight change and HIV clinical stage, which showed that there were distinct patterns of weight loss that occured in stage 4 HIV infection 41…”
Section: Discussionmentioning
confidence: 97%
“…A cohort study in Singapore showed that there was a significant association between clinical disease stage and nutritional status 40. Similarly, the studies at Gonder and West Shewa Zone Ethiopia and Kathmandu Valley, Nepal indicated that the risk of undernutrition increased from WHO clinical stage 1 to 4 23,29,31. There was a relationship between weight change and HIV clinical stage, which showed that there were distinct patterns of weight loss that occured in stage 4 HIV infection 41…”
Section: Discussionmentioning
confidence: 97%
“…In the present meta-analysis, four Ethiopian regions and one administrative town were represented. Five of the studies were from Amhara [4,[26][27][28][29], three from Oromia [24,30,31], five from Southern Region [25,[32][33][34][35], one from Tigray [36], and one from Addis Ababa [37]. However, no studies were located in Benishangul Gumiz, Harari, or Gagmbela regions.…”
Section: Characteristics Of Original Studiesmentioning
confidence: 99%
“…Regarding statistical quality and data presentation, the majority of studies had poor statistical quality and data presentation methods. Besides, to identify factors associated with malnutrition, the majority [4,[24][25][26][27][28][29][30][31][32][33][34][35][36] of studies used binary logistic regression model for analysis, but one of the studies used Pearson correlation coefficients to determine the associations association between nutritional and immunological status [37]. Concerning the model fitness test, only two studies reported about model fitness using Hosmer and Lemeshow goodness of fit test [29,33].…”
Section: Quality Of the Included Studiesmentioning
confidence: 99%
“…Undernutrition is the predominant problem for HIV infected patients. It creates a vicious cycle which may catalyze progression from HIV infection to AIDS [3]. Poor nutrition resulting in weight loss, muscle wasting, weakness, nutrient deficiencies then it leads impaired immune system (poor ability to fight HIV and other infections, increased oxidative stress, increased vulnerability to infections).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of malnutrition by itself can reduce the cluster of differentiation-four (CD4+) T cells and lead to abnormal B-cell response. For HIV infected patients, poor nutrition aggravates the effect of HIV by further decreasing the immune system [3,5], thereby leading in undernutrition, increasing the risk of morbidity and mortality, and potentially reducing the efficacy of antiretroviral therapy (ART) [6].…”
Section: Introductionmentioning
confidence: 99%